EFEKTIVITAS PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING PADA MATERI PERBANDINGAN DI SMP LKIA PONTIANAK - Rapita, Rapita; Hamdani, Hamdani; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out how the effectiveness of learning with the application of Contextual Teaching and Learning  model on comparative materials in class VII SMP LKIA Pontianak. The research method used is descriptive research method. Aspects used to determine the effectiveness of learning using Contextual Teaching and Learning model  are: student learning outcomes, student activities and student responses. Data collection techniques used are measurement techniques, direct observation techniques and indirect communication techniques. Data collection tool used is the test of student learning outcomes, in the form of a description of 4 questions, student activity observation sheets and student response questionnaire. The research data was analyzed descriptively and it was found that the students 'learning completeness was classically fulfilled, the students' activity was obtained during two meetings including the active group and the students responded positive. Learning by using Contextual Teaching and Learning  model on comparative material in grade VII of SMP LKIA Pontianak is said to be effective. Keywords: Effectiveness , Contextual Teaching, Comparative